Technical report of software status in PCs at CAD Lab1 and CAD Lab 2, KAED. - Sa'adon, Norhisham; Ayob, Mohd Fairullazi (2016)
The ICT Unit has prepared existing status of software related, and problems arise at CAD Lab 1 and CAD Lab 2, KAED.